Elderly rural female with giant neglected subcutaneous lipoma of forearm: A case report (Indian Journal of Case Reports, 2025)
Lipomas of the upper limb more than 5 cm are defined as “giant lipomas.” Patients with huge mass on the forearms and hands rarely neglect the problem and seek medical attention because of difficulty in performing day-to-day activities and cosmetic reasons. Here, we present a case of “giant lipoma” of the forearm measuring 10 cm, which was neglected for over 15 years in an 82-year-old female from a rural background. Although extremely rare, “subcutaneous giant lipomas” of the forearm should be considered in the differential diagnosis of painless, slowly growing, neglected swellings. Optimal management requires histopathology to rule out “well-differentiated liposarcomas”. The case highlights the fact that even though lipomas of the upper limb are limited to 2 cm in size, however, if neglected, they may grow enormously and become “giant lipomas” over many years. The case also highlights the uncared chronic medical ailments of elderly rural females in developing countries.